2002
DOI: 10.1002/1522-2683(200209)23:17<2860::aid-elps2860>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

pH Change of buffer solution in a microcapillary chip and its suppression

Abstract: During the electrophoresis separation of B- and T-cells from lymphocytes employing a microcapillary chip, they were found to become inactive in the reservoir after a short time. This was caused by the buffer solution becoming alkaline due to electrolysis. This was considered to take place in chips with small reservoir volumes. The pH change was confirmed by the ISFET (ion-sensitive field effect transistor) embedded in the chip. To suppress the pH change, two methods were studied. One is the insertion of a salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…The buffer pH is the most sensitive parameter in aqueous mobile phases due to the fact that electrochemical processes take place in the microchip reservoirs [126]. To suppress this effect near the electrodes during electric-field-mediated separations, insertion of a salt bridge was proposed [127]. Others recommended a more simple solution by increasing the reservoir volume and/or changing the mobile phase after each run [128].…”
Section: General Considerationsmentioning
confidence: 99%
“…The buffer pH is the most sensitive parameter in aqueous mobile phases due to the fact that electrochemical processes take place in the microchip reservoirs [126]. To suppress this effect near the electrodes during electric-field-mediated separations, insertion of a salt bridge was proposed [127]. Others recommended a more simple solution by increasing the reservoir volume and/or changing the mobile phase after each run [128].…”
Section: General Considerationsmentioning
confidence: 99%
“…For electrophoresis systems, either conventional CE or ME devices, it is well‐known that electrolysis takes place in the solution reservoirs changing the chemical composition of the BGE. Consequently, this affects the solution conductivity and pH values, causing noticeable changes and compromising the repeatability, analytical performance and reliability for quantitative analysis . The electrolysis is still more pronounced when high ionic strength BGEs are used .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, depending on the desirable application, the change in the buffering capacity can be not favorable. Some strategies involving the switching electrodes position in the reservoirs , the addition of solutions with different pH , the continuous washing of the reservoir with fresh BGE solution have also been described to reduce and suppress the electrolysis effects in conventional CE. In 2005, de Jesus and co‐workers proposed the implementation of additional reservoirs linked to principal reservoirs in a conventional CE system through a saline bridge .…”
Section: Introductionmentioning
confidence: 99%
“…In microchip technology [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], several miniaturized devices using micromaching technique such as conventional photolithography and etching technique have been fabricated on silicon or glass substrates [29,30]. Lately, several authors reported polymer-based microchips because they are easily produced by the methods such as molding, casting, or imprinting [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%